Small- to Large-Scale Electron Beam Powder Bed Fusion of Functionally Graded Steels - Carlos Botero; William Sjöström; Emilio Jimenez-Pique; Andrey Koptyug; Lars-Erik Rännar (Journal of Manufacturing and Materials Processing)
The ability to control process parameters over time and build space in electron beam powder bed fusion (PBF-EB) opens up unprecedented opportunities to tailor the process and use materials of a different nature in the same build. The present investigation explored the various methods used to adapt the PBF-EB process for the production of functionally graded materials (FGMs). In this way, two pre-alloyed powders—a stainless steel (SS) powder and a highly alloyed cold work tool steel (TS) powder—were combined during processing in an S20 Arcam machine. Feasibility experiments were first carried out in a downscaled build setup, in which a single powder container was installed on top of the rake system. In the container, one powder was placed on top of the other (SS/TS) so that the gradient materials were produced as the powders were spread and intermixed during the build. The process was later scaled up to an industrial machine setup, where a similar approach was implemented using two configurations of powder disposal: SS/SS + TS/TS and TS/TS + SS/SS. Each configuration had an intermediate layer of powder blend. The FGMs obtained were characterized in terms of their microstructure and local and macromechanical properties. For the microstructural analysis, optical microscopy, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX) were performed on the polished cross-sections. This provided evidence of gradual microstructural and compositional transitions in the samples, with a shift from SS to TS and vice versa. Nanoindentation experiments confirmed that there was a consequent gradient in the hardness, stiffness, and wear ratio from the softer and ductile SS to the harder and stiff TS. Scratch experiments revealed gradual evolution in the sliding wear behavior of the printed materials. A “progressive spring” and a “hardness-tailored punching tool” were fabricated as demonstrators. The results obtained demonstrate the great potential to gradually tailor the composition, microstructure, mechanical properties, and wear resistance by combining different powders, and they suggest that any PBF-EB system can be repurposed to build gradient materials without hardware modification. Potential applications include the tooling industry, where hard and wear-resistant materials are needed for the surfaces of tools, with tougher and more ductile materials used in the cores of tools.